Oral Dictionary - Md. Radzi, Ashylla (Universiti Teknologi Petronas, 2006)
Oral Dictionary application is developed with aim to enhance the existing dictionary, therefore promote flexibility in English dictionary usage through implementation of speech recognition technology. Speech recognition addresses an effective and faster way for word definition searching as word input is retrieved through human's voice, regardless the knowledge on the word spelling where current dictionary relies to. Capability of providing pronunciation playback based on phonetically British English standard overcome the major limitation of current English dictionary. The application is using the text-to-speech (TTS) technology which is different from other commercial dictionary software who use to record each sample of word. In dealing with homophone words (words having similar pronunciation but different spelling), the system successfully provide an approach to reduce the misrecognition. The approach is by providing possible matches, relevant to the phonetic matching of the word. Oral dictionary also offers hassle-free solution to users who only want to hear the pronunciation of the word without having to search throughout the dictionary. Currently, the scope of Oral Dictionary only cover 100 words, within the noun context and using British English (Br.E) standard, as it is English language correctly spoken or written. The application is developed using the combination of vocabulary collection process and incremental delivery model. The major processes involve in vocabulary collection process are words collection, syllabification and ASCII-phonetic transcription. Process activities in Oral Dictionary application will then follow the incremental model which allows system to be reworked in response to change request. Since the output speed is critical, binary search tree algorithm is chosen as best data structure to be implemented in this application to improve the searching time performance. Procedures to obtain the result of the system effectiveness are discussed in this paper, where product evaluation I testing is conducted to two groups of users and the result on searching time comparison, misrecognition rate, verification on British-English standard, system functionality and overall system interface design are discussed in detail throughout this paper.